THE EFFECTIVENESS OF SHORT-FORM VIDEOS TO IMPROVE SPEAKING SKILLS OF FIRST-SEMESTER EFL STUDENTS - Dadan Hidayat; Meiva Eka Sri Sulistyawati; Marsandi Manar (Al-Irsyad: Journal of Education Science, 2026)
This study examines the effectiveness of short-form video platforms in improving speaking skills among first semester EFL students. Speaking remains one of the most challenging English skills for beginner learners, as many struggle with fluency, pronunciation, and confidence when communicating orally. Short form videos, such as TikTok and YouTube Shorts, offer visually engaging content, repetition, and low pressure speaking opportunities. This research employed a pre-experimental one group pre-test and post-test design. A total of 25 first semester English major students participated in eight learning sessions over four weeks, with each session lasting approximately 45 minutes. Speaking performance was measured using a standardized rubric assessing fluency, pronunciation, vocabulary use, and confidence. The results showed an increase from the pre-test mean of 55.20 to the post-test mean of 75.40. A paired-samples t-test confirmed that the improvement was statistically significant (t = 19.15, p < 0.001). The findings demonstrate that short form video based learning supports speaking development and offers interactive, motivating practice for beginner learners. Unlike prior studies focusing mainly on perceptions, this research highlights measurable learning gains. The results suggest that integrating short form videos as a supplementary tool can enhance speaking performance and support technology enhanced instruction.